Prevalence and risk factors of contact dermatitis among clothing manufacturing employees in Beijing: A cross-sectional study. Issue 12 (March 2017) - Chen, Yu-Xin; Cheng, Hai-Yan; Li, Lin-Feng
Abstract : Abstract: Little is known about the epidemiology of contact dermatitis (CD) in the Chinese clothing industry. This study aimed to investigate the prevalence and some risk factors of contact dermatitis among clothing manufacturing employees in Beijing. This cross-sectional study was conducted by interview using self-administered questionnaires and skin examination between May and August in 2016. Five-hundred twenty-nine employees who had worked at sewing, ironing, and as managers at 12 clothing manufacturing factories were studied. The overall 1-year prevalence of CD among the clothing employees was 28.5% (151/529 employees), with significantly higher prevalence among ironing workers (50%) and sewers (31.7%) compared with managers (12.7%; P  < 0.001, n = 529). A significant association was noticed between the 1-year prevalence of CD and types of occupation (sewers and ironing workers versus managers, respectively), exposure to garment materials (leather and feather), dry skin, allergic rhinitis, age, and smoking. Among employees in Chinese clothing industry, sewers and ironing workers had a higher 1-year prevalence of CD than managers. It is noteworthy that exposure to leather and feather materials and the types of manual work are associated with CD, as well as dry skin and allergic rhinitis.